Pengaruh Variasi Volume Konsentrasi Bakteri Bacillus Subtilis Terhadap Sifat Mekanik Beton - Yuridho Alfi; Zulfikar Djauhari; Iskandar Romey Sitompul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Concrete is the most favourite material used in construction. Concrete has some advantages, but in some cases, concrete also has drawbacks. One of the drawbacks founds during the use of concrete is that its tensile strength is low when the tensile strength of concrete is exceeded the cracks will exist. The inovation to solve this is theintroduction of self healing concrete that utilize bacteria bacillus subtilis in a concrete mix. This bacteria can repair cracks in concrete. In this research, bacteria bacillus subtilis were used with different concentration that is 105 cells/20 ml, 105 cells/25 ml and 105 cells/30 ml. Mechanical properties test carried in this research, namelycompressive strenght and flexural strength. The test consist of two loading types namely broken cracks where the concrete was loaded until it fully destroyed and loading up until initial cracks occured. The test was carried after 28 and 56 days of curing. Theresult shown that the concrete with 105 cells/20 ml concentration of bacillus subtilis had the highest compressive strength with increasement by 28,70 % and 34,50 % than normal concrete at 28 and 56 days. The highest flexural strength value has shown in concrete with 105 cells/20 ml.Keyword : Concrete, Cracks, Bacillus Subtilis, Mechanical Properties, Compressive Strength, Flexural Strength